Globular Adiponectin Limits Microglia Pro-Inflammatory Phenotype through an AdipoR1/NF-κB Signaling Pathway - Nicolas, Sarah; Cazareth, Julie; Zarif, Hadi; Guyon, Alice; Heurteaux, Catherine; Chabry, Joëlle; Petit-Paitel, Agnès (Frontiers in Cellular Neuroscience, 2017)
We recently reported that increased levels of Adiponectin (ApN) in the brain led to microglia phenotype and activation state regulation, thus reducing global brain inflammation and depressive-like behaviors in mice. Apart from this, little is known on ApN molecular effects on microglia, although these cells are crucial in both physiological and pathological processes. Here we fill this gap by studying the effects and targets of ApN towards neuroinflammation. Our findings suggest that ApN deficiency in mice leads to a higher sensitivity of mice to neuroinflammation that is due to enhanced microglia responsiveness to a pro-inflammatory challenge. Moreover, we show that globular ApN (gApN) exerts direct in vivo anti-inflammatory actions on microglia by reducing IL-1, IL-6 and TNF synthesis. In vitro, gApN anti-inflammatory properties are confirmed in brain-sorted microglia, primary cultured and microglia cell line (BV2), but are not observed on astrocytes. Our results also show that gApN blocks LPS-induced nitrosative and oxidative stress in microglia. Finally, we demonstrate for the first time that these anti-inflammatory and anti-oxidant actions of gApN on microglia are mediated through an AdipoR1/NF-kappaB signaling pathway.